2020
DOI: 10.1021/acs.analchem.0c02503
|View full text |Cite
|
Sign up to set email alerts
|

Bis(sulfosuccinimidyl)suberate-Based Helix-Shaped Microchannels as Enhancers of Biomolecule Isolation from Liquid Biopsies

Abstract: Most studies of ultrasensitive diagnosis of biomolecules from liquid specimens are limited by problems during sample preparation steps, including enrichment and isolation of biomolecules. Here we report a novel platform combining bis­(sulfosuccinimidyl)­suberate (BS3) and helix-shaped microchannels (BSH) to change the sample preparation paradigm. This BSH system is composed of BS3 for pathogen enrichment and nucleic acid isolation by electrostatic and covalent interaction, and helix-shaped microchannels to min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Our previous studies have demonstrated that various biomaterial composites enable rapid, efficient, and affordable enrichment and separation of viral biomolecules for early clinical diagnosis [13] , [14] , [15] , [16] , [17] . Furthermore, our previous studies have shown that complex devices and expensive reagents are not needed for biomolecule separation steps, including pathogen enrichment and extraction [40] , [41] , [42] , [43] , [44] , [45] , [46] , and can be performed in POC settings. We developed a rapid and efficient SdMDx system with high sensitivity and specificity for the enrichment, amplification, and detection of SARS-CoV-2 and is self-operated and self-diagnosed at home as a POC test.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have demonstrated that various biomaterial composites enable rapid, efficient, and affordable enrichment and separation of viral biomolecules for early clinical diagnosis [13] , [14] , [15] , [16] , [17] . Furthermore, our previous studies have shown that complex devices and expensive reagents are not needed for biomolecule separation steps, including pathogen enrichment and extraction [40] , [41] , [42] , [43] , [44] , [45] , [46] , and can be performed in POC settings. We developed a rapid and efficient SdMDx system with high sensitivity and specificity for the enrichment, amplification, and detection of SARS-CoV-2 and is self-operated and self-diagnosed at home as a POC test.…”
Section: Discussionmentioning
confidence: 99%
“…S1 depicts the overall workflow of the SLIM assay. The principle and the detailed structure of the SLIM assay have been described previously ( 9 , 10 , 13 , 37 ). Briefly, the SLIM assay is based on a combination of a microfluidic platform with low-cost thin film and homobifunctional imidoesters (HIs) reagents for MTB enrichment and DNA extraction from the oral swab samples.…”
Section: Methodsmentioning
confidence: 99%
“…In order to resolve concerns regarding loss of ctDNA, microfluidic-based techniques have been implemented for cfDNA isolation, in which the incorporation of microstructures, such as microbeads [ 84 ], micropillars [ 82 ], and microwells [ 85 , 86 ], enhances the cfDNA/ctDNA extraction performance and consequently shortens the processing time ( Figure 3 A,B). The integration of operations in the microfluidic chips has resulted in higher extraction performance.…”
Section: Recent Technology Advances For Studying Cell-released Biomarkersmentioning
confidence: 99%
“…( B ) In a novel microfluidic chip that contains helix-shaped microchambers to avoid forming bubbles, bis-(sulfosuccinimidyl)suberate reagent is used in lieu of chaotropic and pH modifier reagents to capture cfDNA while this device is capable of enriching pathogens in blood at the same time. Reproduced with permission from [ 86 ]. Copyright 2020 American Chemical Society.…”
Section: Figurementioning
confidence: 99%